Nilai Kepentingan Budaya (Index Of Cultural Significance) Plasma Nutfah Pisang Lokal (Musa Spp.) di Garut Selatan - Ismail, Ade (Jurnal Kajian Budaya dan Humaniora, 2023)
Banana (Musa spp.) Is a fruit that comes from Southeast Asia and has now spread throughout the world. Banana is a crop that people can grow in almost all types of agro-ecosystem and vary the types. In relation to the threat to the existence of germplasm and local knowledge, the solution to prevent the existence is study ethnobotany. Cibalong District of South Garut region is a center of production and commodity of bananas. This study aims to identify the various types of banana (Musa spp.) Which can be used as a potential source of germplasm based study of ethnobotany in Cibalong District. The study was conducted in January 2023 until March 2023 in the district of South Garut Cibalong. This research method is based on determining the location of exploration with purposive sampling method and using participatory approaches PRA (Participatory Rural Appraisal). Based on the survey results revealed that the District Cibalong have a banana crop diversity index of 1.43 is classified by the type of bananas that dominate in a sequence based on the ISI (Importance Score Index) is Pisang Nangka (88.56%), Pisang Ambon (38.78% ), and Pisang Kapas (37.19%). Based on the analysis Index of Cultural Significance Banana Plant in District Cibalong known that Pisang Ambon and Pisang Ambon Jepang with ICS value of each is 52 which has a high value of benefits. It can be concluded that the District Cibalong dominating Banana can fill the needs of the community against the use of banana are high as well.